Benefits of EEG-Neurofeedback on the Modulation of Impulsivity in a Sample of Cocaine and Heroin Long-Term Abstinent Inmates: A Pilot Study: - Corominas-Roso, M. (International journal of offender therapy and comparative criminology, 2020)
The aim of this pilot study was to assess whether neurofeedback (NFB) can be useful in the treatment of impulsive behavior in long-term abstinent cocaine and heroin addicts. A single-blind sham-controlled NFB protocol was carried out to assess the effects of NFB on impulsivity in 20 (10 + 10) cocaine and heroin long-term abstinent addicts (Diagnostic and Statistical Manual of Mental Disorders [4th ed., text rev.; DSM-IV-TR]). Psychotic and neurologic diseases were excluded. Participants underwent 40 NFB sessions based on the very slow cortical potential range. Inhibitory deficits were specifically addressed through right and left prefrontal training. Clinical improvement was measured with Likert-type scales, the Hamilton Depression Rating Scale, and the State-Trait Anxiety Inventory, and impulsivity was assessed using the Barratt Impulsiveness Scale and the Continuous Performance Test. Although the results are preliminary due to the small sample size, the NFB-treated group showed a significant clinical improvement, including symptoms of anxiety and depression, with two differentiated time periods. No significant clinical improvement was found in the control group. A significant decrease in the post- versus pre-treatment measures of global impulsivity, nonplanning impulsivity, and error commission measures was found in the NFB-treated group; effect size (dKorr) in the pre-post control design was moderate. No significant change was found in the control group. Despite the limitations of this study, the results suggest that NFB is better than placebo in improving impulsivity and clinical symptoms of anxiety and depression in long-term abstinent cocaine- and heroin-dependent individuals.